Investigating the kinetics of water-in-crude oil emulsion stability - Adeyemi, B.J. (Asian Research Publishing Network, 2015)
A problem of both fundamental and practical importance to the oil industry is water/oil (w/o) emulsions of which the stability is characterized by creaming or sedimentation, flocculation, coalescence of droplets, and/or phase separation. The knowledge and control of the destabilization mechanisms are crucial for an effective and efficient crude oil dehydration. The aim of this study is to investigate the effect of stability on the aging of w/o emulsions for proper characterization and resolution. Bottle test method is commonly used to determine the stability of emulsions in the oil and gas industry. However, the technique is tedious, time consuming and subjective. Thus, a more robust, accurate and automatic multiple light scattering technique was used to characterize several samples of w/o emulsions of varying water content and salinities. Analyses show that all samples exhibited similar stability behaviour as the original crude oil at ambient conditions. Increase in temperature to 70Â°C led to little sedimentation in all the emulsions. The stability profiles clearly indicated that the emulsions are kinetically stable. Â© 2006-2015 Asian Research Publishing Network (ARPN).